A Politics-of-Naming Analysis of Public Safety and Order in Ukrainian Police and Security Legislation - Olena Salmanova; Oleksandr Prokudin; Oleksii Botnarenko; Vasyl Varivoda; Alla Pyshna; Alla Pohrebniak; Volodymyr Ivantsov (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2026)
Rapid reforms in Ukraine’s security and defence sectors, driven by Russian aggression and martial law, have expanded police roles and highlighted the need for clear public safety legislation. This study examines the usage of Ukrainian terms—публічна (publichna) and громадська (hromadska)— in police and security laws, assessing whether their plurality serves political-legal functions or is due to non-strategic drafting. A hybrid framework was used, including politics-of-naming diagnostics and doctrinal-functional analysis, to identify strategic term usage. A diachronic comparison of the original and amended texts was conducted using Rada records. The core corpus includes the Laws on the National Police (2015), National Guard (2014), National Security (2018), Code of Administrative Offences (1984), Martial Law (2015), and MIA Order No. 706 (2018). Mapping, diachronic verification, and functional testing were used to classify the occurrences of these terms. The results show structured plurality: publichna is focused on Police Law, while hromadska is prevalent in national security, the National Guard, administrative offenses, and martial law legislation, with intra-police-law mixing in Articles 23(1)(27) and 45(3). Three strategic loci were found: definitional asymmetry (hromadska is defined in the National Security Law, publichna is operational in the Police Law), intra-act register switching for group violations, and a diachronic shift under Law No. 1702-IX (effective January 1, 2022) replacing earlier terms with hromadska in Martial Law. The non-strategic remainder reflects referential convergence, offence classification, and subordinate doctrine, including de-escalatory crowd management under the Scandinavian model. The study concludes that full terminological unification would erase doctrinal information; instead, it supports targeted consolidation for non-strategic convergence (via a single amendment to Article 1(1)(3) of the National Security Law) and statutory acknowledgment of differential effects where naming is strategically significant, a need heightened by wartime police power expansion and accountability demands